Pelatihan Mengerjakan Tes Potensi Skolastik Bagi Siswa Kelas XII SMA Untuk Menghadapi Seleksi Nasional Berdasarkan Tes (SNBT) - Hasniati; Husni Agriani; Izmi Alwiah M; awal, Muhammad Awal Nur (PT. Karya Inovatif Nusantara, 2024)
The quality of college graduates can be influenced by selection to enter State Universities (PTN). Therefore, the PTN selection process is an important aspect that needs to be paid attention to by prospective students, parents and the wider community. This service activity aims to provide training on scholastic potential test questions and increase the graduation percentage of Gamaliel Makassar High School students at PTN. The method used is lectures and providing training in taking scholastic potential tests, especially mathematical reasoning. The training participants were 50 class XII students at SMA Gamaliel Makassar. The results of this activity increase students' ability to understand and take scholastic potential tests, especially mathematical reasoning through practice.